Simulation of primary log cutting plan (PPRT) in sawmill wood processing - Vukićević Milan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2011)
A specification of sawn timber is realized based on the previously designed log cutting plan, primary and secondary. The plan of primary log cutting (PPRT) has its verbal and mathematical interpretations. The theoretical aspect of PPRT design reported in the literature has great disadvantages. As it is based on the description and empirical combinations, such PPRT could hardly be evaluated as optimal. In addition to the above weakness, there is another one, i.e., the fact that the problem of PPRT design is reduced to a mono-criterion problem, i.e. the minimisation of total waste. If the problem of PPRT design is approached systematically, it is clear that the minimisation of total waste is only one out of a series of goals that a PPRT should fulfil. Nevertheless, the procedure presented in the literature is deeply rooted in practice. This paper, based on the on simulation principle, presents a modern procedure of PPRT design which consists of a number of phases. The first phase includes computer support in the design procedure of log cutting plans and also, a mono-criterion decision making in the selection of log cutting plans which ensure the minimal total waste per PPRT. The second phase includes the definition of another two criteria which are decisive for the optimal quality of PPRT. They are the log prices and the profit. Altogether 84 (eighty-four) cutting plans were designed and 4 (four) PPRTs. The solution of the problem, i.e. the design of an optimal PPRT in the conditions of three criteria, is based on multicriteria decision making using the method of Analytical Hierarchy Processes - AHP. The calculation is computed by the software Program Criterion Decision Plus - Version 3.0 Student version, InfoHarvest.Inc. In the study simulation of PPRT design, the optimal plan was PPRT3. The presented three criteria are not the final number. The inclusion of additional relevant criteria will depend on the inventiveness of the manager.